A victory for statins or a defeat for diet policies? Cholesterol falls in Poland in the past decade: A modeling study. (15th April 2015) - Bandosz, Piotr; O'Flaherty, Martin; Rutkowski, Marcin; Kypridemos, Chris; Guzman-Castillo, Maria; Gillespie, Duncan O.S.; Solnica, Bogdan; Pencina, Michael J.; Wyrzykowski, Bogdan; Capewell, Simon; Zdrojewski, Tomasz
Abstract: Aim: The present study is aimed to examine whether recent changes in population total cholesterol (TC) levels in Poland might be attributed to increased use statins. Methods: Two independent, nationally representative cross-sectional studies were conducted in adults aged 18–79 years in 2002 (n = 2993, mean age 46.2 years) and 2011 (n = 2413, mean age 45.8 years), including measurements of TC in venous blood samples. The mean change of TC between 2002 and 2011 was assessed. Then the expected therapeutic reduction in TC level in 2011 attributable to statins only was calculated based on already published statin effectiveness data. Uncertainty was quantified using probabilistic sensitivity analysis. Results: Statin uptake in Poland rose to 11.2% in 2011 (95% Confidence Intervals (CI): 10% to 12.5%) and approximately 32% (95% CI: 28.4 to 36.0%) in subjects aged 60–79 years. Mean TC in Poland in 2002 was 5.35 mmol/l, and fell by 0.21 mmol/l (95% CI: 0.14 to 0.28) by 2011. This fall would have been only 0.03 mmol/l (95% CI: − 0.04 to 0.10) for the total adult population and 0.06 mmol/l (95% CI: − 0.09 to 0.22) in people aged 60–79 years if statins had not been used. Statin use thus apparently explained approximately 85% (95% CI: 49% to 120%) of the observed decrease. Conclusion: Between 2002 and 2011, statin medications apparently explained a large part of the observed fall in population cholesterol level, suggesting very little changes in population TC attributed to dietary changes.